Perception of the headmaster towards the implementation of the policy: english for teaching mathematics and science - Da-I, Naruemon; Salleh, Mohamad Johdi; Hussien, Suhailah (2010)
The main purpose of this study is to examine the perceptions of selected primary school headmasters regarding the implementation of English Teaching for Mathematics and Science (ETeMS). The study was conducted on seventy nine selected primary schools in Malaysia. The study employed the quantitative method used a set of questionnaire and in-depth survey questions. Statistical analysis included descriptive approach, frequency and percentage. The questionnaire was distributed by post to 79 headmasters from selected primary schools including the National Primary Schools (Sekolah Kebangsaan), National-type Primary Chinese School (Sekolah Jenis Kebangsaan China), National-type Primary Tamil School (Sekolah Jenis Kebangsaan Tamil), and the government-aided school of the missionary schools. Findings of the study showed that most of the headmasters supported ETeMS, but they faced some problems and challenges in the implementation of ETeMS, particularly when most of the Mathematics and Science teachers and also the students were not proficient in English.